Accountability for the Implementation of State Finances (APBN) for the Covid-19 Pandemic Program and National Economic Recovery (PC-PEN) in the Fiscal Year 2020 - Posma Sariguna Johnson Kennedy (Asia Pacific Fraud Journal, 2022)
This study aims want to see the results of the examination of the Supreme Audit Agency (BPK) in its reporting to the House of Representatives of the Republic of Indonesia (DPR-RI)  concerning the study of State Finance to fulfill the task of inspection of Accountability for Implementation of the Budget (APBN) for the Fiscal Year 2020 related explicitly with the COVID-19 Handling and National Economic Recovery Program (PC-PEN), in connection with the Internal Control System (SPI) and Compliance with Legislation. The research method in this study is to use qualitative methods through the literature or secondary data. The process of collecting data in this research is by using the form of documentation and literature study, namely by collecting and studying data, especially those taken from the results of the BPK examination. Although the BPK’s examination results gave an “Unqualified Opinion” (WTP), BPK still saw that it did not fully achieve the effectiveness, transparency, accountability, and compliance of State Finance management and responsibilities in the PC-PEN Program in the COVID-19 pandemic emergency conditions.